физиканинг механика бўлимини муаммоли таълим технологияларидан фойдаланиб ўқитишнинг педагогик асослари - Ибадуллаев, А.А. (SCIENCE and SOCIETY, 2023)
This article discusses problematic educational technologies and the pedagogical foundations of their application in higher education. The author gave information about the importance of problem education in teaching the mechanics section, creating a problem program, forming knowledge and skills that a teacher should be able to know and apply in problem learning.